Usefulness of anorectal and endovaginal 3D ultrasound in the evaluation of sphincter and pubovisceral muscle defects using a new scoring system in women with fecal incontinence after vaginal delivery - Murad-Regadas, Sthela M. (2017)
Purpose This study aims to evaluate pubovisceral muscle and anal sphincter defects in women with previous vaginal delivery and fecal incontinence and to correlate the findings with the severity of symptoms using the combined anorectal and endovaginal 3D ultrasonography with a new ultrasound scoring system. Methods Consecutive female patients with previous vaginal delivery and fecal incontinence symptoms were screened. Fecal incontinence was assessed with the Cleveland Clinic Florida fecal incontinence scale, and the extent of defects was assessed by an ultrasound score based on results of anorectal and endovaginal 3D ultrasound. Fecal incontinence was assessed with the Cleveland Clinic Florida fecal incontinence scale. Results Of 84 women with previous vaginal delivery and fecal incontinence, 21 (25%) had intact pubovisceral muscles and anal sphincters; 63 (75%) had a pubovisceral muscle or anal sphincter defect, or both. Twenty-eight (33%) had a pubovisceral muscle defect [23% with an external anal sphincter (EAS) defect or combined EAS/internal anal sphincter defects; 11% with intact anal sphincters]. Thirty-five (42%) had intact pubovisceral muscles and an anal sphincter defect. Compared with women with intact pubovisceral muscles/anal sphincter defects, patients with pubovisceral muscle defects had significantly higher incontinence scores and significantly higher ultrasound scores indicating more extensive defects. Incontinence symptoms correlated positively with the ultrasound score, measurements of sphincter defects, and area of the levator hiatus. Conclusions Evaluation of both pubovisceral muscles and anal sphincters is important to identify defects and determine treatment for women with fecal incontinence after vaginal delivery. The severity of fecal incontinence symptoms is significantly related to the extent of defects of the pubovisceral muscles and anal sphincters.